Fiducial Governance An Australian republic for the new millennium - Power, John (Australia and New Zealand School of Government (ANZSOG), 2010)
Fiducial Governance: An Australian republic for the new millennium represents an attempt to grapple with the challenges of designing governance regimes suited to the new millennium. Power's monograph asserts the need for the reform of Australian governance and charts Australia's fitful progress towards a republican future. Along the way he sketches a framework for constitutional reform, mindful of the strengths and weaknesses of the current system of government and the contest of ideas about the role and configuration of Australian Heads of State. Long a frustrated Australian republican, Power contends that the republican log jam is due in significant part to a lack of respect shown by the republican policy community to the contribution long made to good governance by monarchical heads of state. This monograph seeks to draw lessons from this experience, so as to make the republican venture one of substance for the Australian public. In so doing, Power draws on a range of republican, indigenous and feminist writings in order to develop a new framework of 'fiducial governance' aimed at enhancing the trustworthiness and integrity of our institutions of governance, thereby paving the way for the replacement of the monarch by a directly elected head of state. This is an erudite and thoughtful book that will be of interest to those with an interest in systems of governance and to constitutional scholars, whether they be republicans or monarchists.